Influence of Perceptions and Preparedness of Senior High School Teachers based on their Qualifications towards Professional Teacher Licensing in Ghana - Amoah, Samuel Obed; Britwum, Francis; Adu-Gyamfi, Kenneth; Nyamekye, Francis; Anyagre, Palmas; Ahiatrogah, Paul Dela (International Journal of Educational Technology and Learning, 2020)
The study sought to explore the influence of perceptions and preparedness of senior high school teachers based on their qualifications towards professional teacher licensing in Ghana. The study was motivated by three research hypotheses. A sample size of 278 senior high school teachers in Ashanti, Ghana region was selected using multi-stage sampling technique. Data were analysed using independent sample t-test and one-way ANOVA to answer the research hypotheses. The study revealed that male and female teachers had similar perceptions and preparation towards the teacher licensing. This was because male teachers did not differ significantly compared to their female counterparts on teachers’ perceptions and preparedness towards the teacher licensing in Ghana. The study also found that teachers who hold a bachelor degree have similar perceptions and perceived preparedness towards the teacher licensing policy compared to certificate ‘A’, diploma, and post-graduate degree holders. This is because one-way between-groups ANOVA test shows that the teachers did not differ statistically in their perceptions and perceived preparedness towards teacher licensing in Ghana in relation to teacher qualification. The study recommended that outreach unit of GES should use the mass media and profession development to help teachers have answers to their questions about the policy. The study again recommended that GES and teacher unions should use professional development programmes to educate and prepare teachers for the implementation of the policy.